Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Melalui Aplikasi Marketplace Online Di Kalangan Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Sumatera Utara - Warhamna Syahri; Muhammad Arif; Nurwani Nurwani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research aims to determine and analyze the factors that influence consumer decisions through online marketplace applications among students at the Faculty of Economics and Islamic Business, North Sumatra State Islamic University with a total of 5838 active students. The sampling technique used in this research was a simple random sampling technique with 98 respondents from the Faculty of Economics and Islamic Business who made purchases online. The method used in this research is an associative quantitative approach using a multiple linear regression analysis model. The results of the first research on free shipping show that it has a significant effect on online purchasing decisions. Both payment methods show that they do not significantly influence online purchasing decisions. All three consumer reviews show that they have a significant influence on online purchasing decisions. The four ease of use shows that it has a significant influence on online purchasing decisions. Simultaneously, the results of this research influence online purchasing decisions.